2020
DOI: 10.1002/aisy.202000159
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Gallium‐Based Liquid Metals: Mechanisms and Applications in Biomedical Sensors and Soft Actuators

Abstract: This review focuses on surface modifications of liquid metal (LM). Gallium (Ga) and Ga-based LMs show the promising ability to maintain metallic properties under large mechanical strains when encapsulated inside an elastomer matrix. [1-7] This property is useful in a variety of applications, including wearable/deformable devices, sensors, and soft actuators-the focus of this special issue. There are several motives for creating soft and stretchable devices. For example, devices that are soft and flexible can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 119 publications
(220 reference statements)
0
41
0
Order By: Relevance
“…Thus, the annealing of PaLMPs in an acidic condition partially removes of the oxide shell, which extrudes out the gallium. We hypothesize that the removal and reformation of the oxide layer at the interface strengthens the adhesion of PaLMP lm to the substrate 21,33 . We have furthermore observed that only the lm printed with an AA-containing ink on a heated substrate was intrinsically conductive, with a resistivity of 6.67x10 −7 Ωm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the annealing of PaLMPs in an acidic condition partially removes of the oxide shell, which extrudes out the gallium. We hypothesize that the removal and reformation of the oxide layer at the interface strengthens the adhesion of PaLMP lm to the substrate 21,33 . We have furthermore observed that only the lm printed with an AA-containing ink on a heated substrate was intrinsically conductive, with a resistivity of 6.67x10 −7 Ωm.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the abovementioned drawbacks of bulk LM, LM particle-based approach has been actively studied where the outer oxide layer can restrain its uid-like behavior 20,21 . However, the formation of the native oxide layer deteriorates the electrical conductivity since the oxide is an insulator.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Interestingly, the oxide layer that forms on the surface of EGaIn is found to be composed of gallium oxide. 27,28 The preferential growth of gallium oxide is due to the more favourable Gibbs free energy of oxide formation for gallium when compared with indium. By exploiting this concept, elements with thermodynamically more favourable oxide formations can be alloyed into gallium-based liquid metals to produce oxides of the dissolved elements.…”
Section: Torben Daenekementioning
confidence: 99%
“…This oxidation can affect the apparent surface tension and electrical properties of nanocomposite film. 5,6 SEM images show that the EGaIn is present mainly close to the surface of the film, and the nanocomposite shows a rough surface morphology with cavities (Figures 2B and S2a-c). It is thought that the oxide layer forms quickly on the EGaIn surface, causing the surface to be rough and nonconductive.…”
Section: Nanocomposite Fabrication and Characterizationmentioning
confidence: 99%